Representation Of Caste, Gender And Power Politics In Premchand’s Godaan- A Gift Of A Cow - Surendra Kumar Gupta, Surendra Kumar Gupta (International Journal of Psychosocial Rehabilitation, 2012)
The politics of caste and power are tangled and lead to web of deceit. Caste is an inherent part of social and cultural fabric of Indian life. But our contradictory experience makes us thrive to trace or attempt to understand the causes of caste and gender discrimination. However, from time to time sensitive readers can analyze and interpret the representation one finds in the imaginary situations, characters and the dilemmas which are modeled after real people and places in various genres. But in due course the literary text seizes to limit itself to the time period in which it was produced. The significance of the work depends on its characteristic of shifting relevance. This paper primarily focuses on “how caste forms a criterion for development or fall of an individual in his/her own community and society?” and trace the lineage between caste and power; gender and shift in power structure in Premchand’s novel Godaan. Some critics say that Premchand presented downtrodden/ untouchables as idiots, insensitive and lazy. But here I would like to argue that the writer has employed different mode to depict caste based society, their suffering and revolt. It is a natural human tendency to take it as it comes when suffering crosses the limit of tolerance. That is what is shown in the imaginary but deep rooted world of fiction of the writer.